Mediterranean Coral Provinces as a Sponge Diversity Reservoir: Is There a Mediterranean Cold-Water Coral Sponge Fauna? - Santín, Andreu; Grinyó, Jordi; Uriz, Maria Jesús; Lo Iacono, Claudio; Gili, Josep Maria; Puig, Pere (Frontiers in Marine Science, 2021)
Cold-water coral reefs (CWC) are known to be biodiversity hotspots, however, the sponge assemblages found to dwell within these habitats haven not been studied in depth to date in the Mediterranean Sea. The present article provides the first insight on the associated sponge fauna of the recently discovered CWC communities on the Catalan Margin and, to a lesser extent, the Cabliers Coral Mound Province, while also reviewing the current knowledge of the sponge fauna dwelling in all the Mediterranean CWC provinces. In regards to the studied areas, some rare species are cited for the first time in the Mediterranean or redescribed, while two of them, Hamacantha (Hamacantha) hortae sp. nov. and Spongosorites cabliersi sp. nov. are new to science. At a basin scale, Mediterranean CWC appear as poriferan biodiversity hotspots, yet current diversity values on each site rather represent a small fraction of its actual fauna. Additionally, the existence of an endemic sponge fauna exclusively dwelling on CWC is refuted. Nonetheless, the sponge fauna thriving in Mediterranean CWC appears to be unique, and different from that of other Atlantic regions. Finally, with the current knowledge, the sponge fauna from the Mediterranean CWC is grouped in three distinguishable clusters (Alboran Sea, Western and Eastern Mediterranean), which appears to be determined by the basins water circulation, specially the Levantine Intermediate Water and the Atlantic Water following a western-eastern pattern from the Strait of Gibraltar to the Adriatic Sea. Overall, sponge living in Mediterranean CWC are still poorly explored in most areas, yet they appear to be good candidates for biogeographical studies. Zoobank Registration: LSID urn:lsid:zoobank.org:pub:E58A3DFF-EDC5-44FC-A274-1C9508BF8D15.